2019
DOI: 10.3390/ijerph16245013
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effect of the Environment and Commuting Flow from/to Epidemic Areas on the Spread of Dengue Fever

Abstract: Environment and human mobility have been considered as two important factors that drive the outbreak and transmission of dengue fever (DF). Most studies focus on the local environment while neglecting environment of the places, especially epidemic areas that people came from or traveled to. Commuting is a major form of interactions between places. Therefore, this research generates commuting flows from mobile phone tracked data. Geographically weighted Poisson regression (GWPR) and analysis of variance (ANOVA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Three significantly high-risk clusters were identified. The studies conducted in dengue non-endemic regions indicated that the core contributors to the spatial heterogeneity of dengue were: urban village; urban-rural fringe zone; dense population, human mobility, gross domestic product per capita; Normalized Difference Vegetation Index; number of imported cases; subway network; density of road networks ( 22 , 24 27 ). The three high-risk clusters we identified were characterized by a dense population, high human mobility, high incidence of imported cases, dense road networks, and advanced economy.…”
Section: Discussionmentioning
confidence: 99%
“…Three significantly high-risk clusters were identified. The studies conducted in dengue non-endemic regions indicated that the core contributors to the spatial heterogeneity of dengue were: urban village; urban-rural fringe zone; dense population, human mobility, gross domestic product per capita; Normalized Difference Vegetation Index; number of imported cases; subway network; density of road networks ( 22 , 24 27 ). The three high-risk clusters we identified were characterized by a dense population, high human mobility, high incidence of imported cases, dense road networks, and advanced economy.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] The influence of climate change and travel to/from endemic countries are important factors leading to the disease outbreak. [ 20 ] An analysis of imported cases from 2014 to 2018 in China showed that the dengue patients were mainly aged between 21 and 50 years old made up the most farmers and unemployed people. [ 21 ] Among the 231 dengue patients admitted to our hospital, those in the < 60 years age group accounted for the largest proportion, followed by the 60 to 80 years age group, which may be attributed to the fact that more elderly patients come to see a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar and Agrawal [140]; Sintayehu et al [141] These predictors included built-up area (explained by the Normalized Difference Builtup Index-NDBI), population, vegetation (explained by the Normalized Difference Vegetation Index-NDVI), land surface temperature (LST), water (explained by the Normalized Difference Water Index-NDWI), and moisture (explained by the Normalized Difference Moisture Index) [126,127,[140][141][142][143][144]. It is noted that the indices utilized to represent the environmental factors are well established in the literature and have been extensively used to study several environmental problems.…”
Section: Evaluating Different Spatial Socio-environmental Factors Of Df: a Multivariate Analysismentioning
confidence: 99%